Characterization of fuel injection and mixing process in a GDI engine using CFD - Dongre, Varun (My University, 2021)
In this thesis, computational fluid dynamics(CFD) simulations were carried on a gasoline direct injection (GDI) engine to study the thermal behavior, Piston fuel film mass accumulation, Heat release rate and emissions with different injection timings, piston temperatures and boundary temperatures. Simulating an internal combustion (IC) engine on any CFD platform is challenging because of its complex moving geometries, varying conditions, complex chemistry, and changing fluid structure. Gasoline Direct Injection can help increase engine efficiency and specific power output and reduce exhaust emissions. Also, simulation of internal combustion engines offers a significant challenge in the field of CFD research. Moving boundaries of the solution domain, caused by valves’ motion, piston leads to deformation of the computation grid, which decreases the quality of the results. The GDI surface file was imported onto the Converge work-space to change case setup parameters depending on which fuel was used. Also, changes were made during the simulations to check the resulting behavior with varying parameters. Once after the initial description of the case setup process, studies of fuel film accumulation on the piston were investigated. The simulations showed that a mixture of Primary Reference Fuels (PRF) provided the best results for piston fuel film accumulation, spray-distribution, in-cylinder temperature, and pressure at particular injection timing and piston temperature. Lastly, standard physical models such as the Extended Coherent Flamelet Model (ECFM) combustion model, Imposed Spark Stretch Ignition model (ISSIM) ignition model, and K-epsilon turbulence model were used for simulations.